Determining the Need for Client 24-Hour Supervision: A Cross-Sectional Survey of Occupational Therapists. Issue 1 (2nd January 2021) - Flemming, Kendra; Ferri, Richard; Rose, Mathew A.; Maranan, Avelino (Jun); Nalder, Emily
Abstract: This study explored how private practice occupational therapists determined whether their clients' need 24-hour supervision, including assessments used, modes of clinical reasoning and therapists' confidence in their determinations. Survey data from 90 participants were analyzed using descriptive statistics. Participants reported using 166 different assessments to inform decisions about 24-hour supervision and most frequently engaged in pragmatic and conditional reasoning. On average, therapists perceived that they were confident or very confident in their determinations. There is variability in how therapists assess and reason through when 24-hour supervision may be required. Research to develop practice guidelines in this area is needed.